(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article is devoted to the study of the psychology of modern fathers, analyzing the changing role of fatherhood in society and its social, psychological and cultural aspects. In the modern model of fatherhood, the father is not only an economic provider, but also takes an active part in the upbringing of children, satisfying their emotional needs and forming them as individuals. The article discusses the basic principles of paternal psychology, new approaches in society and the impact of paternal responsibility on the family environment. The relationship between modern fathers and their impact on the psychology of children are also studied. The article serves to better understand the psychological aspects of family upbringing and provides practical recommendations aimed at improving the role of fatherhood in modern society.